1995 Aspergillus Bibliography - John Clutterbuck (Fungal Genetics Reports, 1995)
This bibliography attempts to cover genetical and biochemical publications on Aspergillus nidulans and also includes selected references to related species and topics. I would be grateful for publication lists and reprints, especially for papers in books and less readily available periodicals. Entries have been checked as far as possible, but please tell me of any errors.